PERANCANGAN DAN IMPLEMENTASI SUPPLY CHAIN MANAGEMENT PADA PRODUKSI PLASTIK KEMASAN - D. Hedin Purnama; Purwanto; Husnul Khotimah; Ibrahim Latief (Institut Sains dan Teknologi Al-Kamal, 2022)
Supply Chain Management is a method or technique for companies to maximize their business processes. Using the supply chain management method is expected that the company can fully integrate its business processes starting from customer requests, ordering raw materials for production purposes, production stages to ensuring products reach customers according to the desired schedule. This relationship method certainly has a very positive impact for the company and its partners, especially customers who are the measuring point for the success of a company. If the company can ensure that the goods are delivered to the customer on time, it is impossible for the customer to always maintain a good relationship with the company, therefore the supply chain management system is very much needed to imrpove customer relationship management This research aims to 1) build supply chain management information system, 2) access eazily on business process of supply chain management information system. This supply chain management information system uses waterfall methode and XAMPP, PHP, MySQL and Sublime Text 3 as software.